113 The swinburne slot: a clinic-based service for deteriorating patients with interstitial lung disease. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Kavanagh, Emily; Palmer, Eve; Harper, Julie; Donaldson, Claire; John Simpson, A; Forrest, Ian; Bourke, Anne-Marie
Abstract : Introduction and objectives: Patients with interstitial lung disease (ILD) can deteriorate quickly. It can be difficult to determine whether this is due to disease progression or other potentially reversible processes. Such patients are often known to multiple services; carer feedback in 2016 highlighted it is difficult to know who to approach. In response, the Newcastle ILD team introduced a weekly 30 min rapid access clinic slot (Swinburne Slot, SS) with the aim of determining reversibility and to support patients in their preferred place of care. Our objective was to evaluate this service, which may have practice implications for other teams. Methods: We collected data on how the SS was utilised between 12/09/2016 and 21/03/2017. This included appointment outcome; for example, further imaging or referral to specialist palliative care. Additionally, we collected data on acute hospital admissions within 30 days. Data were obtained using electronic medical records and telephone calls to General Practitioners. Results: The SS was utilised 24 times during the 28 week evaluation period. The most frequent clinic outcomes were adjustment to medication (n=19) and same day palliative care review (n=12). There could be multiple outcomes per patient. Six patients were admitted to hospital within 30 days with an ILD-related problem. Six patients died between the start of the evaluation and the end of data collection. Conclusions: Carer feedback highlighted a deficiency in our service. Our response, the SS, was well utilised, resulting in adjustment to patient management and improved access to palliative care. We present the SS as a workable model which could be replicated by other multidisciplinary teams.